Bibliographic survey of the causal relationship between Cardiovascular diseases and Covid-19 (Research, Society and Development, 2022)
This study aims to perform an integrative literature review to understand the causal relationship between cardiovascular diseases and Covid-19 and to point out new updates on the subject. Currently, the world faces the pandemic of coronavirus disease 2019, a severe acute respiratory syndrome caused by coronavirus SARS-CoV-2, having as one of the most frequent pathological consequences cardiovascular diseases. Infection-related myocardial damage can occur due to multiple reasons, including: decreased oxygen levels due to acute respiratory distress syndrome, damage from direct viral invasion of cardiomyocytes with subsequent cell death, microthrombus formation, and a persistent inflammatory state. Viral invasion impairs the contractile function of cardiomyocytes, triggers electrical dysfunction and alters the balance of the Reinnine Angiotensin Aldosterone system. To date, epidemiological studies indicate that a high pathological relationship between Covid-19 and cardiovascular diseases where both pathologies complement each other to generate simultaneous harmful damage. Given the current compelling evidence that myocardial injury intensifies the severity of Covid-19, cardiac management should be a priority for physicians and health professionals. The harmful relationship between SARS-CoV-2 infection and cardiovascular diseases is notorious, but new searches to better understand its etiology are crucial.